Sea Cucumber Trade and Sustainability in Türkiye: Progress, Problems, and Opportunities - Mehmet Aydın; Kadir Aksay; Uğur Karadurmuş (Aquatic Sciences and Engineering)
Türkiye is rich in sea cucumber stocks and therefore offers ample opportunities for becoming the leading exporter in the world. This study aims to explore sea cucumber export trends in Türkiye for the first time using annual series data. Export-related information has been compiled from official data records and interviews with the managers of exporting companies. The data set includes the sea cucumber export process in Türkiye, export destinations, temporal shifts in export, and export tendency according to Harmonized System codes. Türkiye is in a competitive and advantageous position in the global market. This study has revealed that the export of sea cucumber products from Türkiye has performed well and seems to have grown well over the years, mainly when exporting to high-demand countries. Investing in the sea cucumber sector will also pay off through long-run economic growth and development. COVID-19, high commodity prices and inflation, and the Russia-Ukraine conflict have been identified as problems in sea cucumber exports. To reach long-term export targets, Türkiye should develop trading policies toward export performance and sustainable stock management. Maintaining exports in high-value-added markets and increasing financial support for exporters have been determined as the fundamental elements of these policies.